Applying Next-Generation Sequencing Platforms for Pharmacogenomic Testing in Clinical Practice - Tafazoli, Alireza; Guchelaar, Henk-Jan; Miltyk, Wojciech; Kretowski, Adam J.; Swen, Jesse J. (Frontiers in Pharmacology, 2021)
Pharmacogenomics (PGx) studies the use of genetic data to optimize drug therapy. Numerous clinical centers have commenced implementing pharmacogenetic tests in clinical routines. Next-generation sequencing (NGS) technologies are emerging as a more comprehensive and time- and cost-effective approach in PGx. This review presents the main considerations for applying NGS in guiding drug treatment in clinical practice. It discusses both the advantages and the challenges of implementing NGS-based tests in PGx. Moreover, the limitations of each NGS platform are revealed, and the solutions for setting up and management of these technologies in clinical practice are addressed.